Investigation of oil-water flow regimes and pressure drops in mini-channels - Bultongez, Kevin K.; Derby, Melanie M. (My University, 2017)
Oil-water flow regimes were studied in 2.1 mm and 3.7 mm borosilicate glass tubes; both tubes exhibit Eötvös numbers less than one and therefore surface tension forces may be more important in these mini-channels compared to larger diameter tubes. A closed-loop, adiabatic experimental apparatus was constructed and validated using water. This study focused on tap water and two mineral oils (i.e., Parol 70 and 100) with a density of 840 kg/m3 but a factor of two difference in viscosity. Experiments included a wide range of oil superficial velocities (e.g., 0.84–6.84 m/s for D = 2.1 mm and 0.27–3.30 m/s for D = 3.7 mm) and water superficial velocities (e.g., 0.21–7.69 m/s for D = 2.1 mm and 0.07–4.96 m/s for D = 3.7 mm). Stratified, annular, intermittent, and dispersed flow regimes were observed in both tubes, although the annular flow regime was more prevalent in the smaller tube. Pressure drops increased with decreasing tube diameter and were flow regime dependent. Flow maps were created for these mini-channels and equations adapted from Brauner and Maron (1999) were used to predict the flow regime transitions. The effects of viscosity were modest, although increased oil viscosity enhanced stability of oil-water flows.
Citation: Bultongez, K.K., Derby, M. M. (2017).Investigation of oil-water flow regimes and pressure drops in mini-channels. International Journal of Multiphase Flow,96,101-112. https://doi.org/10.1016/j.ijmultiphaseflow.2017.07.001
Keywords: Mini-channel; Oil-water; Flow regime; Flow regime map